Perbandingan Fiqih Dan Undang-Undang Nomor 23 Tahun 2004 Tentang Kekerasan Dalam Rumah Tangga Perspketif Zawajir Dan Jawabir - Rahman, Aris (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
The issue of domestic violence is one of the phenomena of various types of violence that occur today. As with other cases of violence that continue to increase, domestic violence is increasing from year to year. The purpose of this writing is to examine kFiqh and Legal Provisions on Domestic Violence in Indonesia Andanalyzing the provisions of Fiqh and Law Number 23 of 2004 reviewed from the theoretical perspectiveZawajir And Speech. The method used is a normative legal method with a qualitative approach that refers to Fiqh and legal norms contained in laws and regulations and legal norms that apply in society. The type of research that will be used is literature, by conducting a study of primary and secondary legal materials. The results of this study are the Zawajir and Jawabir Theory of Domestic Violence in Islamic law and Law Number 23 of 2004 concerning Domestic Violence are seen as Preventive and Repressive efforts, including in Islamic law as Preventive efforts can be done with Early Religious Education, Marriage as a Sacred Bond, Premarital Guidance, Tarbiyah and Da'wah through sermons. While in Law Number 23 of 2004 concerning Domestic Violence can be done with Education and Socialization, Family Guidance, Training and Capacity Building of Law Enforcement Officers, Increasing Access to Services. As a Repressive effort in Islamic law can be through Advice and Stages of Settlement, Bringing in a Mediator, Divorce as a Last Resort, and Criminal Sanctions in Islamic Law. Meanwhile according to Law Number 23 of 2004 concerning Domestic Violence can be done with Reporting and Handling of Cases, Temporary and Long-Term Protection, Prosecution and Criminalization and Rehabilitation of Perpetrators. This study found that the zawajir andjawabir approaches in fiqh and Law Number 23 of 2004 both emphasize preventive and repressive efforts in dealing with domestic violence.